Preparation of CuO Nanorods by Thermal Oxidation in Ozone Ambient - Ha, Tran Thi; Thanh Cong, Bach; Hai, Pham Nguyen; Hoang, Nguyen; Chinh, Ho Van; Huong, Bui Thu; Linh, Nguyen Thuy; Son, Bui Truong; Quynh Hoa, Tran Thi; Nguyen Viet, Tuyen (VNU Journal of Science: Mathematics - Physics, 2022)
CuO nanorods were prepared by thermal oxidation method in ozone ambient. The effect of annealing temprature in the range from 400 to 600 o C on morphology and structure of nanorods was studied thouroughly by scanning electron microscopy (SEM) and X-ray diffraction, combining with energy dispersive spectroscopy (EDS) and Raman spectroscopy. The results showed that annealing temprature strongly affected the structure and morphology of the produced CuO nanorods. The most uniform nanorods with highest crystal quality were obtained when annealing temperature is from 450 to 500 °C and annealing time was 2 h as suggested by SEM images together with Raman results.